Aplasmomycin and boromycin are specific inhibitors of the futalosine pathway. (November 2018) - Shimizu, Yohei; Ogasawara, Yasushi; Matsumoto, Atsuko; Dairi, Tohru
Abstract We searched for specific inhibitors of the futalosine pathway, non-canonical pathway of menaquinone biosynthesis operating inHelicobacter pylori, from metabolites produced by actinomycetes. Aplasmomycin, a boron-containing macrodiolide, was isolated fromStreptomyces sp. K15-0223 as a specific inhibitor of the futalosine pathway. We also showed boromycin, an analog of aplasmomycin, had similar activity.